Identification of novel TMEM231 gene splice variants and pathological findings in a fetus with Meckel Syndrome - Zhang, Qian; Yang, Shuya; Chen, Xin; Wang, Hongdan; Li, Keyan; Zhang, Chaonan; Liao, Shixiu; Qin, Litao; Hou, Qiaofang (Frontiers in Genetics, 2023)
Background: Meckel Syndrome (MKS, OMIM #249000) is a rare and fatal autosomal recessive ciliopathy with high clinical and genetic heterogeneity. MKS shows complex allelism with other related ciliopathies such as Joubert Syndrome (JBTS, OMIM #213300). In MKS, the formation and function of the primary cilium is defective, resulting in a multisystem disorder including occipital encephalocele, polycystic kidneys, postaxial polydactyly, liver fibrosis, central nervous system malformations and genital anomalies. This study aimed to analyze the genotype of MKS patients and investigate the correlation between genotype and phenotype. Methods: A nonconsanguineous couple who conceived four times with a fetus affected by multiorgan dysfunction and intrauterine fetal death was studied. Whole exome sequencing (WES) was performed in the proband to identify the potentially pathogenic variant. Sanger sequencing was performed in family members. In silico tools were used to analyse the pathogenicity of the identified variants. cDNA TA-cloning sequencing was performed to validate the effects of intronic variants on mRNA splicing. Quantitative real-time PCR was performed to investigate the effect of the variants on gene expression. Immunofluorescence was performed to observe pathological changes of the primary cilium in kidney tissue from the proband. Results: Two splice site variants of TMEM231 (NM_001077418.2, c.583-1G>C and c.583-2_588delinsTCCTCCC) were identified in the proband, and the two variants have not been previously reported. The parents were confirmed as carriers. The two variants were predicted to be pathogenic by in silico tools and were classified as pathogenic/likely pathogenic variants according to the American College of Medical Genetics and Genomics guideline. cDNA TA cloning analysis showed that both splice site variants caused a deletion of exon 5. RT-PCR revealed that the expression of TMEM231 was significantly decreased and immunofluorescence showed that the primary cilium was almost absent in the proband's kidney tissue. Conclusion: We reported the clinical, genetic, molecular and histochemical characterisation of a family affected by MKS. Our findings not only extended the mutation spectrum of the TMEM231 gene, but also revealed for the first time the pathological aetiology of primary cilia in humans and provide a basis for genetic counselling of the parents to their offspring.